2022
DOI: 10.46766/thegms.medethics.22021403
|View full text |Cite
|
Sign up to set email alerts
|

Patient Betrayal: The Corruption of Healthcare, Informed Consent and the Physician-Patient Relationship

Abstract: The purpose of this study is: first, to review disciplinary threats made to healthcare professionals by their governing bodies in the US; and second, to review medical literature for complications related to the COVID-19 vaccines and data from the Vaccine Adverse Event Reporting System (VAERS), particularly those related to pregnant women and women of reproductive age. The authors also aim to bring attention to the populace, healthcare workers, and healthcare administrators that illegal and unconstitutional ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The vaccine is in trial phase and has been linked to not only instant side effects but also short to medium-term side effects [44]. Thorp et al (2022) highlighted just a few of these side effects, such as miscarriage, foetal death and malformation, chronic autoimmune disease, permanent immune deficiency syndrome, chronic permanent CNS diseases and chronic cognitive disorders, seizure disorders and neonatal/infant cancers; and this only refers to foetuses and infants [46]. Not enough time has passed since administration of the first injections to know what the long-term effects might be.…”
Section: Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vaccine is in trial phase and has been linked to not only instant side effects but also short to medium-term side effects [44]. Thorp et al (2022) highlighted just a few of these side effects, such as miscarriage, foetal death and malformation, chronic autoimmune disease, permanent immune deficiency syndrome, chronic permanent CNS diseases and chronic cognitive disorders, seizure disorders and neonatal/infant cancers; and this only refers to foetuses and infants [46]. Not enough time has passed since administration of the first injections to know what the long-term effects might be.…”
Section: Protectionmentioning
confidence: 99%
“…Pfizer's documents show lipid nanoparticles with their mRNA cargo being distributed throughout the entire body and passing through the blood brain, placental and foetal blood brain barriers and concentrate in the ovaries. From US life insurance reports we know that the all-cause death rates were up 40% in ages 18-64 years by the end of Q3 2021, and according to life insurance companies there are 100,000 excess deaths per month in the US in all age groups, which cannot be attributed to COVID-19 alone [46].…”
Section: Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the compelling evidence that these "vaccines" dramatically increased miscarriages, fetal malformation, neonatal deaths and other newborn baby complications, the media and the CDC continued to promote injecting pregnant women (Wolf, 2022b, Thorp 2022.…”
Section: Cdc Massages Data: Says Unvaccinated Persons Carry and Trans...mentioning
confidence: 99%
“…Why are these individuals and the media supporting such draconian programs directed at pregnant women? Not only have they been working relentlessly to hide the data demonstrating that in fact the injected women are undergoing a miscarriage rate eight time higher than normal, but the incidence of severe infant malformations is skyrocketing among the "vaccinated" (Thorp, 2022)? Why did the New England Journal of Medicine publish an article proclaiming safety of these injections in pregnant women when the article has been shown, beyond all doubt, to contain manipulated data to falsely show safety, when in fact the study demonstrated that women in their 1 st trimester who received the injection had an 82% higher miscarriage rate (Shimabukuro et al, 2021)?…”
Section: Introductionmentioning
confidence: 99%